Comparison of factors affecting platelet reactivity in various platelet function tests. (4th July 2019) - Choi, Sun Young; Kim, Moo Hyun
Abstract: Previous studies have reported that various factors affect ADP-induced platelet reactivity during clopidogrel therapy. The aim of this study was to determine whether clinical and laboratory variables for platelet reactivity during dual antiplatelet therapy (DAPT) are dependent on the assay used. We enrolled 904 patients receiving DAPT following coronary intervention. Platelet reactivity was measured using three methods: the VerifyNow P2Y12 assay, multiple electrode aggregometry (MEA) ADP assay, and the light transmittance aggregometry (LTA) ADP assay at 24–48 h following coronary intervention. The VerifyNow results demonstrated a significant inverse correlation with hematocrit value ( r = –0.268, p < 0.0001); however, MEA results had no such correlation with hematocrit ( r = 0.044, p = 0.188). There was a positive correlation between the MEA results and platelet count ( r = 0.255, p < 0.0001). LTA was weakly influenced by hematocrit ( r = –0.064, p = 0.057) and platelet count ( r = 0.069, p = 0.040). Gender (odds ratio 1.53, 95% CI 1.10–2.14, p = 0.013) and hematocrit (odds ratio 0.91, 95% CI 0.88–0.94, p < 0.0001) were the independent variables for HPR by VerifyNow. Smoking (odds ratio 0.38, 95% CI 0.16–0.94, p = 0.036) and platelet count (odds ratio 1.01, 95% CI 1.00–1.01, p < 0.0001) were independent factors for HPR when using the MEA assay, whereas platelet count (odds ratio 1.00, 95% CI 1.00–1.01, p = 0.006) was identified as the only independent variable for HPR when using LTA. The incidence of HPR and the influencing variables involved are dependent on the platelet function test used.